Assessment of Cardiac Function and Prevalence of Sleep Disordered Breathing using Ambulatory Monitoring with Acoustic Cardiography – Initial Results from SWICOS - Peter, Bauer; Patricia, Arand; Dragana, Radovanovic; Franco, Muggli; Andreas, W. Schoenenberger; Renate, Schoenenberger-Berzins; Gianfranco, Parati; Augusto, Gallino; Georg, Ehret; Paul, Erne (Journal of Hypertension and Cardiology, 2018)
The aim of this study was to assess the use of ambulatory acoustic cardiography during the initial data collection of the longitudinal study of a rural population in Switzerland (n=297, mean age 48.9 ±16.5 years, 57% female). Ambulatory acoustic cardiography non-invasively can assess sleep disordered breathing (SDB) and provides markers of left ventricular systolic and diastolic dysfunction. The percentage of the third heart sound detected during sleep decreased significantly across age groups (age < 40 years, 40-60 years, > 60 years) for both genders (males, p=0.04; females, p=0.02). The percentage of a fourth heart sound detected exhibited an increasing trend for both genders with age suggesting increased diastolic dysfunction with aging. Mean electromechanical activation time (EMAT) during sleep was within the normal range across age groups and both genders (male 93.7 ± 11.6 ms, female 94.6 ± 13.0 ms), and did not vary significantly with age. A large proportion of subjects had a high likelihood of sleep disordered breathing (17.6%). Baseline characteristics categorized by SDB severity indicate increasing age, male gender and being overweight (BMI ≥ 25) to be associated with greater SDB severity. Acoustic cardiography findings categorized by SDB severity reveal increased nocturnal non-dipping heart rate, presence of atrial fibrillation, prolonged QRS duration and QTc interval, increased percentage of fourth heart sound detected, and longer EMAT to be significantly associated with greater SDB severity. Overall, acoustic cardiography detected a very low prevalence of systolic dysfunction, age-related increases in diastolic dysfunction and a moderate prevalence of sleep disordered breathing.
Keywords: epidemiology; health status; risk factors; prevention